A systematic review of sport-based adolescent mental health awareness programmes - Nora Sullivan; Gavin Breslin; Marian McLaughlin; Stephen Shannon; Gerard Leavey; Martin Dempster (PLoS ONE, 2025)
Background Adolescent mental illness is of increasing concern, with a high prevalence in many parts of the world. Early engagement, detection and receiving support are warranted to reduce the severity of symptoms. Increasing mental health literacy (MHL) through sport to adolescents is one way of engaging young people and signposting them to services. The aim of this systematic review was to identify the effect of interventions, risk of bias, and theoretical application in sport-based adolescent mental health awareness programmes. Methods: Six electronic databases (MEDLINE Ovid, PsycINFO, Scopus, CINAHL, SPORTDiscus, Cochrane) were searched from 2012 to September 2022 (updated January 2024). Inclusion criteria stated the sample had to include adolescents aged 11–17 years, include mental health outcomes, and a sport component. Results: Six studies met the inclusion criteria. Sample size ranged from nine to 816 participants. Four distinct sport-based programmes were evaluated, with three interventions applying a psychological behaviour change theory. The results of the interventions indicated positive effects on several indices of MHL, such as increased knowledge of mental health, depression and anxiety literacy and the recognition of disorders, increased resilience and intentions to provide help. It was found that addressing stigma remains a challenge. The interventions produced the most significant effects for those who scored lower at baseline measures and the younger cohorts. Conclusions: Sport is useful for the engagement and dissemination of mental health awareness information to adolescents. Given the limited number of psychological theory informed interventions, there is a need for further interventions that explicitly adopt behaviour change theories and improve the quality of research design for these interventions. The findings from this review will be of interest to health promotion and public health practitioners and those designing mental health awareness programmes for adolescents. Systematic review registration PROSPERO CRD42022312260